X-RAY AND NEAR-INFRARED OBSERVATIONS OF THE OBSCURED ACCRETING PULSAR IGR J18179-1621 - Nowak, M. A.; Paizis, Adamantia; Rodriguez, Jerome; Chaty, Sylvain; Del Santo, Melania; Grinberg, Victoria; Wilms, Jörn; Ubertini, P.; Chini, R. (Astrophysical Journal, 2012)
IGR J18179-1621 is an obscured accreting X-ray pulsar discovered by INTEGRAL on 2012 February 29. We report on our 20 ks Chandra-High Energy Transmission Gratings Spectrometer observation of the source performed on 2012 March 17, on two short contemporaneous Swift observations, and on our two near-infrared (K-s, H-n, and J(n)) observations performed on 2012 March 13 and 26. We determine the most accurate X-ray position of IGR J18179-1621, alpha(J2000) = 18(h)17(m)52.(s)18, delta(J2000) = -16 degrees 21'31.'' 68 (90% uncertainty of 0.'' 6). A strong periodic variability at 11.82 s is clearly detected in the Chandra data, confirming the pulsating nature of the source, with the light-curve softening at the pulse peak. The quasi-simultaneous Chandra-Swift spectra of IGR J18179-1621 can be well fit by a heavily absorbed hard power law (N-H = 2.2 +/- 0.3 x 10(23) cm(-2) and photon index Gamma = 0.4 +/- 0.1) with an average absorbed 2-8 keV flux of 1.4x10(-11) erg cm(-2) s(-1). At the Chandra-based position, a source is detected in our near-infrared (NIR) maps with K-s = 13.14 +/- 0.04 mag, H-n = 16 +/- 0.1 mag, and no J(n)-band counterpart down to similar to 18 mag. The NIR source, compatible with 2MASS J18175218-1621316, shows no variability between 2012 March 13 and 26. Searches of the UKIDSS database show similar NIR flux levels at epochs six months prior to and after a 2007 February 11 archival Chandra observation where the source's X-ray flux was at least 87 times fainter. In many ways IGR J18179-1621 is unusual: its combination of a several week long outburst (without evidence of repeated outbursts in the historical record), high absorption column (a large fraction of which is likely local to the system), and 11.82 s period does not fit neatly into existing X-ray binary categories.
Keywords: accretion; accretion disks; binaries: close; stars: individual; X-rays: binaries